Wayang Tengul Art Performance: A Study of People’s Appreciation of Wayang Tengul Art - Nurdiyana, Tutung (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
Wayang tengul is one type of wayang (puppet) belonging to Indonesia existing in Sidobandung Village, Balen Subdistrict, Bojonegoro Regency. This wayang is still preserved and found attractive by society until now. This wayang preservation depends on society’s appreciation as the audience of wayang tengul and is one of the most important factors for the success of a performance. Therefore, this research attempts to describe how people in Sidobandung Village appreciate wayang tengul. This qualitative research was conducted in Sidobandung Village. It shows how the people highly appreciate wayang tengul art since this wayang art is unique, not strictly bound by wayang common practice, performed interactively between dalang (puppeteer), gending (Javanese music) and audience and laden with guidance presented in fresh jokes.